2020
DOI: 10.1101/2020.09.07.286286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss ofPrdm12during development, but not in mature nociceptors, causes defects in pain sensation

Abstract: Prdm12 is as a key transcription factor in nociceptor neurogenesis. Mutations of Prdm12 cause Congenital Insensitivity to Pain (CIP) due to failure of nociceptor development. However, precisely how deletion of Prdm12 during development or adulthood affects nociception is unknown. Here, we employ tissue- and temporal-specific knockout mouse models to test the function of Prdm12 during development and in adulthood. We find that constitutive loss of Prdm12 causes deficiencies in proliferation during sensory neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
1
4
1
Order By: Relevance
“…Landy and colleagues recently published the results of bulk RNA-seq analysis of DRGs of adult Prdm12 knockout mice, generated as we have done by crossing Avil CreERT2 mice to Prdm12 fl/fl mice. 30 In contrast to our results, they found that almost all DEGs were decreased in mutant mice. Comparing their transcriptomic data to our list of DEGs identified in DRG, surprisingly, only 1 common gene was found, Chrna6 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Landy and colleagues recently published the results of bulk RNA-seq analysis of DRGs of adult Prdm12 knockout mice, generated as we have done by crossing Avil CreERT2 mice to Prdm12 fl/fl mice. 30 In contrast to our results, they found that almost all DEGs were decreased in mutant mice. Comparing their transcriptomic data to our list of DEGs identified in DRG, surprisingly, only 1 common gene was found, Chrna6 .…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the effects of Prdm12 deficiency on transcription, we found that mice lacking Prdm12 exhibit normal thermosensation and itch response. Unaltered response to noxious cold is somehow surprising given the fact that we found that Trpm8 expression is reduced in Prdm12 icKO mice, as observed by Landy et al (2021). This unaltered response to acute noxious cold may be because of the fact that Trpm8 expression is reduced but not abolished in DRG neurons of icKO mice.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…PRDM12 function was subsequently assayed in mammalian model systems. While germline deletion of PRDM12 and conditional knockout of PRDM12 in the embryonic neural crest was neonatal lethal, conditional knockout of PRDM12 in embryonic DRGs produced viable offspring (Kokotović et al, 2021; Landy et al, 2021). These mice displayed increased mortality and exhibited corneal abrasions and facial scarring similar to what is seen in human CIP patients; they also displayed decreased baseline sensitivity to mechanical and cold stimulation, decreased chemical sensitivity to capsaicin injection, and decreased itch response to chloroquine and histamine.…”
Section: Resultsmentioning
confidence: 99%